Effects of pre-oxidation temperature and air volume on oxidation thermogravimetric and functional group change of lignite. - Baoshan Jia; Zihao Chai; Wanting Zhao; Xian Wu (PLoS ONE)
To investigate the impact of the oxidation temperature and variations in airflow conditions on coal spontaneous combustion characteristics, pre-oxidized coal samples were prepared using a programmed temperature rise method. Synchronous thermal analysis experiments and Fourier transform infrared spectroscopy were conducted to explore changes in the thermal effects and functional group content of the coal samples, respectively. The results indicate that variations in pre-oxidation conditions primarily in fluence the activation temperature and maximum weight loss temperature of the coal samples, while exerting a lesser impact on the critical temperature and ignition point. Variations in air volume conditions predominantly affect the content of Ar-C-O- and -CH2 & -CH3 in the oxygen-containing functional group region. The trend of the average activation energy within a conversion rate range of 0.2 to 0.6 of pre-oxidized coal samples changing with the increased of pre-oxidation temperature under the air flow conditions of 25mL/min and 50mL/min is consistent, but opposite to that under the air flow conditions of 100mL/min and 200mL/min. Compared to raw coal, under an airflow rate of 50 mL/min and when oxidized to 110°C, the coal sample exhibits an increase in the content of OH…OH, accompanied by reductions in the critical temperature, activation temperature, ignition point, and maximum weight loss temperature to varying degrees, thereby rendering it more susceptible to oxidative spontaneous combustion.